Analysis: the rape of Palestinian men - Jahangir, Junaid; Long, Jennifer (My University, 2025)
Palestinian survivors of sexual abuse receive tragically little attention in Western media. This includes Palestinian women, who have been sexually assaulted for decades. In contrast, a lot more mainstream media space was afforded to Israeli victims of sexual abuse from October 7th even though some of that narrative has been problematized. Indeed, an article from Fairness and Accuracy in Reporting reviewed New York Times coverage of sexual violence in Israel and Palestine over 11 months and noted a disproportionate focus on allegations of sexual assault committed by Palestinians (80%) versus allegations against Israelis (20%). The reporting on Israelis also avoided labelling these acts as sexual violence. Analyses have shown that Canadian media coverage disproportionately humanizes Israelis compared to Palestinians. The lack of coverage contributes to a broader narrative that overlooks Palestinians’ suffering.
Keywords: survivors of sexual abuse; Palestinian men; media bias